Value-Based Trade Competitiveness: Maqāṣid al-Sharī‘ah, VBI, and the Challenges and Opportunities for OIC Countries - Imron, Ali; Fadli, Royyan; Kholis, Nur; Musfiqoh, Siti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – This study examines the structural challenges and emerging opportunities shaping international trade among Islamic countries within the context of global economic transformation. Methodology – Employing a descriptive qualitative approach based on literature from international institutions and scholarly sources, the analysis integrates conventional trade theory, competitive advantage perspectives, and Islamic economic principles grounded in Maqāṣid al-Sharī‘ah and Value-Based Intermediation (VBI). Findings – The findings indicate that OIC member states continue to face persistent constraints, including low export diversification, non-tariff barriers, fragmented halal certification systems, technological disparities, and limited readiness for digital and green economic transitions. These challenges collectively weaken trade competitiveness and inhibit effective participation in global value chains. Conversely, significant opportunities arise from the expansion of digital trade, renewable energy development, Islamic finance innovation, and strengthened intra-OIC cooperation. Conclusion – The study argues that integrating Islamic value-based frameworks with structural and technological reforms can enhance competitiveness, promote sustainability, and support a more coherent trade governance system. Contribution/Novelty – The contribution of this research lies in providing a comprehensive analytical framework that links empirical trade dynamics with normative Islamic principles, thereby offering strategic insights for developing value-oriented, inclusive, and resilient international trade policies among Islamic countries